Perceived Organizational Support: Linking Human Resource Management Practices with Affective Organizational Commitment, Professional Commitment and Turnover Intention - Lew, Tek (Journal of International Management Studies, 2009)
The main objective of this conceptual paper is to examine the role of perceived organizational support (POS) to link the four (4) human resource management practices namely pay satisfaction, career development opportunities, work/family support and leader-member exchange and affective organizational commitment, professional commitment and turnover intention of faculty members working for private higher education institutions in Malaysia. This paper will mainly be driven theoretically by the social exchange theory, the concept of perceived organizational support (POS) which is the commitment of the organization to the employee, the norm of reciprocity, the organizational support theory as well as the other relevant literature in the human resource management and organizational behaviour research. This paper contributes to the limited body of knowledge about the psychological processes underlying the formation of organizational commitment through the perspectives of the social exchange theory (Blau, 1964) and the organizational support theory (Eisenberger, et al., 1986; Eisenberger et al., 2001).